The knowledge and the opinion of patients on the government package called ‘fast oncological therapy’ – a pilot survey study - Ręka, Gabriela; Paprzycka, Karolina; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: The fast oncological therapy was introduced in 2015 by a set of legal arts called an oncology package. Its main assumption was to reduce malignant neoplasms by improving the availability of diagnostics and complex treatment. The aim of the study is to analyse the level of knowledge and to learn opinions of patients of the Center of Oncology of the Lublin Region on the fast oncological therapy. Material and methods: Material used in the analysis is the results of survey conducted on a group of patients from different hospital departments. An original anonymous questionnaire with 25 open and closed questions was used. Out of 130 distributed questionnaires, 44 items were returned completed. The program used to perform the statistical analysis was Statistica PL 10.0 2011 StatSoft. Results: The survey indicates that 43.2% of respondents have ever heard about fast oncological therapy, 27.3% declare knowledge of the therapy's basic aims. In a detailed knowledge test 1 point was awarded for every right answer. A maximum of 11 points could be obtained, with the average score being 2.3 points. 22.7% of patients surveyed did not answer any question correctly. No relationship has been found between age, place of residence or duration of the disease and the level of knowledge about the fast oncological therapy. 36.4% of respondents admit that they have been treated in accordance with the fast oncological therapy, but most of those who did (75%), evaluate its effect positively. Conclusions: The patients' knowledge about the package is extremely low. Only a minority of respondents are aware of the package's existence. However, the patients judge the changes introduced by fast oncological therapy as positive.